Becoming an Antiracist Educator - Lynch, Brian (Schools (Chicago, Ill.), 2023)
This article describes the author's journey into the world of teaching. The author begins with his transition into academia and his goal to become an antiracist educator. He reflects on teaching (and observation) moments in the classroom and moves to descriptions and insights of specific lessons teaching Eve Ewing's "1919" poetry collection and Octavia Butler's "Parable of the Sower." He concludes that there is no closure in the journey to becoming an antiracist educator.